1955
DOI: 10.1021/ja01606a075
|View full text |Cite
|
Sign up to set email alerts
|

Bolaform Electrolytes. IV. Conductance of α,ι-Bispyridinium Polymethylene Bromides and β,β'-Bisquaternary Substituted Diethyl Ethers in Methanol

Abstract: aqueous layer was extracted with 700 ml. of chloroform and the chloroform extracts were combined and washed with 1350 ml. of water. The chloroform solution was concentrated under reduced pressure to a volume of 450 ml. The mixture was cooled to 0-5 °. To the slurry was added slowly 3150 ml. of petroleum ether, the temperature being maintained at 0-5°. After stirring for one hour, the ketol III was collected on a filter, washed with a mixture of petroleum ether and chloroform (4:1), finally with petroleum ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1957
1957
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The ionic association and the reaction of the ions with the solvent in water-ethanol mixtures were investigated for N-ethyl-4-cyanopyridinium iodide [46] as a function of the concentration of the dissolved salt, and the data were analyzed with regard to the existence of solvent-separated ion pairs. The temperature variations of the association constants were established.…”
Section: Salts Containing Aromatic Cations (Without Heteroatoms In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic association and the reaction of the ions with the solvent in water-ethanol mixtures were investigated for N-ethyl-4-cyanopyridinium iodide [46] as a function of the concentration of the dissolved salt, and the data were analyzed with regard to the existence of solvent-separated ion pairs. The temperature variations of the association constants were established.…”
Section: Salts Containing Aromatic Cations (Without Heteroatoms In Thmentioning
confidence: 99%
“…In [46] the dependence of the limiting solubility and the dissociation constants of bolaform electrolytes (a type of electrolyte in which the charges are separated by the chain of atoms in a polyion) was discussed: 1,2-ethane-, 1,4-butane-, and 1,10-decane-N,N′-bispyridinium dibromides, and also the diethyl ether of bis-β-pyridinium dichloride.…”
Section: Salts Containing Aromatic Cations (Without Heteroatoms In Thmentioning
confidence: 99%
“…Often the form of the frequency dispersion was not f-1/2. Nichol and Fuoss (43) observed ]-1 frequency dependence in methanol solutions, while De Nooijer (44) reported that in molten nitrate melts plots of measured resistance vs. 1-1/2 were not linear, but approached linearity as the frequency approached infinity. His values of measured resistance at 20 kHz only differed from values extrapolated to infinite frequency by about 0.1%.…”
Section: Frequency Response--as Seen In Tablementioning
confidence: 99%
“…Rm: Rs +Rz [5] Frequency dispersion of the measured resistance has been observed in organic solvents (43) and in molten salts. Often the form of the frequency dispersion was not f-1/2.…”
Section: Frequency Response--as Seen In Tablementioning
confidence: 99%
“…With a conductance cell that Is not. a pure series RC combination, some frequency dependence of measured or calculated Rs still may be observed, and extrapolation to infinite frequency as a function of w or a more appropriate empirical function of frequency still may be required (15,24) This extrapolation should not, however be based on an incorrect equivalent circuit of the cell. The fact that one does not know the exact equivalent circuit of the cell does not eliminate the necessity of a choice if a resistance is to be calculated from the measurable impedance and phase angle, and the series RC combination is the best approximation in many cases.…”
Section: Balance Of Pure Resistancesmentioning
confidence: 99%